THE IMPORTANCE OF MOTIVATION GIVEN BY PARENTS IN LEARNING A FOREIGN LANGUAGE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Learning foreign languages by children is becoming more popular among parents. The aim of the study is to identify the level of motivation of parents to teach English to senior preschool children and to establish the relationship between the level of motivation of parents and preschoolers' attendance of English classes.